1991
DOI: 10.1103/physrevb.44.4296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface and physical confinement on the phase transitions of cyclohexane in porous silica

Abstract: We have measured the specific heat (C~) of cyclohexane at 120& T &300 K when cyclohexane was physically restricted in porous Spherosil (silica) samples of pore radii 4, 7.5, 15, 30, and 62.5 nm. The behaviors of the monoclinic-to-cubic structural transition and of the melting transition of cyclohexane were determined.As expected, both transition temperatures, i.e. , solid-solid and melting, inversely scaled with the pore radius (R~}. It is argued that the surface heterogeneity, the presence of hydroxyl groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 25 publications
8
77
1
Order By: Relevance
“…there is large and important group of restricted geometry objects, namely materials confined within porous media (hereinafter we will call them confined materials -CM). In recent years properties of CM and in particular various types of phase transitions (PT) (superconducting [1,2], superfluid [3,4], melting-freezing [5,6,7,8,9,10,11] and others PTs [12,13,14,15,16,17,18,19,20,21,22] in different CM have been extensively studied by different experimental methods including calorimetry [5,7,20], NMR [9,21], ultrasonic [8,9] and dielectric [12,14,15] measurements, Raman [10,13], X-ray [12,16,17,18] and neutron scattering [10,14,22,23,24,25,26], differential thermal analysis [19] etc. It has been shown that CM can form either a system of isolated particle...…”
Section: Introductionmentioning
confidence: 99%
“…there is large and important group of restricted geometry objects, namely materials confined within porous media (hereinafter we will call them confined materials -CM). In recent years properties of CM and in particular various types of phase transitions (PT) (superconducting [1,2], superfluid [3,4], melting-freezing [5,6,7,8,9,10,11] and others PTs [12,13,14,15,16,17,18,19,20,21,22] in different CM have been extensively studied by different experimental methods including calorimetry [5,7,20], NMR [9,21], ultrasonic [8,9] and dielectric [12,14,15] measurements, Raman [10,13], X-ray [12,16,17,18] and neutron scattering [10,14,22,23,24,25,26], differential thermal analysis [19] etc. It has been shown that CM can form either a system of isolated particle...…”
Section: Introductionmentioning
confidence: 99%
“…The temperatures of solid I -solid II transition, that is the transition to plastic phase, observed for TBC confined to CPG with 15.6 nm as well as 7.4 nm pore diameter is also depressed, 5 K and 21 K, respectively. Similarly to the results for cyclohexane [21,23,25], the extent of the depression, is smaller than that of the freezing temperatures, 17 K and 43 K, respectively.…”
Section: Dscmentioning
confidence: 54%
“…The first peak at 247 K is assigned to liquid-solid I transition, while the latter to the solid I -solid II (at 214 K) and solid II -solid III (182.4 K) transitions. The characteristic larger peak at 214 K marks the transition to the plastic phase, in which molecules are very mobile and orientationally disordered [21][22][23].…”
Section: Dscmentioning
confidence: 99%
“…The melting and freezing within porous glasses have been observed for materials such as water, organic liquids [5,6], metals with low melting point [7][8][9][10][11], helium [12], oxygen and some other simple liquids [13][14][15]. The ferroelectric phase transition within porous glass has been observed for NaNO 2 and K 2 HPO 4 [16,17].…”
Section: Introductionmentioning
confidence: 99%